New caricatures and an unknown text by Abraham Valdelomar - Thissen, Servais (2017)
This article rescues a series of new caricatures ofAbraham Valdelomar as well as "Horas de lucha"('Hours of struggle'), a text of the Conde de Lemos(Earl of Lemos, aristocratic pseudonym) that up tonow has not been compiled as part of his work. Withthe publication of these illustrations and this paper, itis intended to contribute to the systematization of thecomplete work of Valdelomar.